THE FEATURES OF SOCIAL FEARS MANIFESTATION IN STUDENT YOUTH (Psychology Travelogs, 2023)
The article interprets the concept of "fear" as a state of agitation, anxiety, and unease caused by the anticipation of something unpleasant or unwanted. Fear is portrayed as a signal of danger threatening the organism and is independent of human will. Sociological and psychological research confirms that the most common sources of fears and apprehensions are the peculiarities of social relations.The author notes that among the negative factors hindering the development of social skills are social fears. While these fears are an integral part of socialization, they can pose obstacles to the successful acquisition of social skills in a student environment. Based on a theoretical and methodological analysis of scientific literature, it is clarified that social fear is an emotion arising from social circumstances, rooted in previous experiences, and anticipates potential dangers in social situations.Factors playing a crucial role in the formation of fears in youth are identified, including an uncertain future, the desire for independence, underdeveloped self-assessment, unsuccessful attempts to lead an "adult" life, family conflicts, and existing anxieties. The text emphasizes the significance of self-assessment in shaping future professionals and highlights the psychological weight of the fear of social rejection in the context of social adaptation and relations.The passage underscores that the challenges and requirements associated with higher education can evoke the fear of failure among students. This fear may hinder successful learning, as students may fear receiving poor grades, not meeting teachers' expectations, or being unable to cope with academic workload. The fear of failure in interpersonal relationships influences the way individuals interact and communicate with others, particularly in situations where one fears not meeting social expectations, satisfying others, or dealing with complex or conflict situations in interpersonal relationships.
Keywords: student youth; fear; social fear; self-assessment; fear of social rejection; fear of failure; fear of failure in interpersonal relationships